From truman to trump: the ethos of presidents of the united states in speeches at united nations organization general assembly - Lima de Oliveira, Érico (2019)
This article aims to analyze the ethos of presidents of the United States of America in speeches delivered at the UN General Assembly, from President Harry Truman to President Donald Trump. At first, an analysis of the rhetoric in the construction of ethos will be performed, as the character of the speaker, as the image that it transmits to his audience. Thus, the analysis of the means of persuasion, of the essential characteristics of the speaker, and the existence of a pre-discursive ethos and a discursive ethos will be fundamental for a second analysis of the ethos of the American presidents. Rhetoric is an important tool used in international law, through which countries establish their relations, their interests, and their negotiations in the international system.